2021
DOI: 10.3892/wasj.2021.90
|View full text |Cite
|
Sign up to set email alerts
|

Influence of toxic metal exposure on the gut microbiota (Review)

Abstract: The gut microbiota (GM) is composed of >100 trillion different organisms, including bacteria, viruses, fungi, archaea and protists, coexisting in a complex system. The GM can be very sensitive to drugs, diet or even environmental pollutants. In the present review, recent data related to the interaction between the GM and heavy/toxic metals are discussed, focusing on the compounds most widely distributed in the environment or considered biopersistent. There are data to suggest that exposure to metals can alter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 106 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…Noteworthy are occupational exposures to pesticides, used for the control of pests, which could affect human GM ( 54 ). Heavy metals (HMs) including cadmium, lead, arsenic, and other metals can contaminate soils and reach the human GM through the food chain ( 55 ). Exposures to environmental toxicants have been studied primarily for long-term systemic health effects on respiratory disease and cognition, among others, but there is growing evidence that these components also affect the GM.…”
Section: Bidirectional Interaction Between Environmental Chemicals An...mentioning
confidence: 99%
“…Noteworthy are occupational exposures to pesticides, used for the control of pests, which could affect human GM ( 54 ). Heavy metals (HMs) including cadmium, lead, arsenic, and other metals can contaminate soils and reach the human GM through the food chain ( 55 ). Exposures to environmental toxicants have been studied primarily for long-term systemic health effects on respiratory disease and cognition, among others, but there is growing evidence that these components also affect the GM.…”
Section: Bidirectional Interaction Between Environmental Chemicals An...mentioning
confidence: 99%
“…Once metals enter the GI system, the gut microbiome potentially mediates metal toxicity through biochemical reactions of oxidation or reduction. However, heavy metals promote oxidative stress and disrupt healthy microbiomes in humans, thereby inciting dysbiosis [ 113 , 192 ]. When protective commensal microbial communities enter a state of dysbiosis, there is an increase in the toxic effects of heavy metals [ 26 ] and long-term oxidative stress insults, which are in turn associated with neurobehavioral and neurological pathologies [ 193 ].…”
Section: Heavy Metals and The Gut–brain Axismentioning
confidence: 99%
“…The human GI tract contains a diversity of metabolites produced by the microbiota. These microbiota metabolites mediate gut–brain communication by transiting to the CNS, thereby modulating oxidative stress and promoting microglia activation [ 192 , 295 ]. Oxidative stress disrupts gut and BBB barriers, leading to α-synuclein misfolding, aggregation, and subsequent neuronal damage in both ENS and CNS [ 183 ].…”
Section: Heavy Metals and The Gut–brain Axismentioning
confidence: 99%
“…Another study demonstrated that toxic metals could promote metabolic disorders, such as harmful effects on the gut microbiota and the development of diseases, such as obesity, type 2 diabetes mellitus, metabolic diseases and cancer (52). P. pashia fruit also contains toxic metals such as cadmium, zinc, nickel, lead and mercury, although within the recommended limits (53).…”
Section: Anti-inflammatory and Antiproliferative Activitiesmentioning
confidence: 99%